The Deliberation System in Islamic Politics and Leadership of Islamic Organizations in North Sulawesi Province, Indonesia - Nasruddin Yusuf; Abd. Latif Samal; Nurlaila Harun (Khazanah Sosial, 2022)
This research aims to describe and analyze how the deliberation system in Islamic politics and leadership conducted by the Prophet and his caliphs with the system of deliberation in Islamic politics and leadership conducted by Islamic organizations in North Sulawesi Province. This research is descriptive qualitative research. To get the data, the researcher did interviews with several managers from the three Islamic Organizations: the Muhammadiyah, the Nahdlatul Ulama (NU) and the Syarikat Islam (SI). Documentation data is also carried out to find out the annual work program and management activities. The results showed that Islamic organizations such as Muhammadiyah, NU and SI also conducted deliberations. Muhammadiyah holds deliberations every five years and involves regional managers, branches, and sub-branches. Muhammadiyah's political stance is not affiliated with political parties and focuses on the development of people who are knowledgeable and intelligent. Then, the concept of the NU deliberation is also contained in its household article. The NU conducts regional deliberations involving branch managers and sub-branch managers. The Nu's vision and mission is to become a religious and civic organization. The SI also conducts deliberations, namely annual deliberation, and daily deliberation. In its concept and perspective, the SI will further strengthen the organization's commitment through a populist economy and preaching based on the Qur'an and hadith. Thus, there are differences of views and principle related to the deliberation system of the Islamic politics and leadership from the three Islamic organizations even though the legal basis is the same, namely the Qur'an and Hadith.